Strengthened of AES Encryption Algorithms within New Logic Topology - Vahid Rashtchi; Seyyed Hamidreza Mousavi (Majlesi Journal of Electrical Engineering, 2024)
Side-channel attacks are considered to be the most important problems of modern digital security systems. Today, Differential Power Attack (DPA) is one of the most powerful tools for attacking hardware encryption algorithms in order to discover the correct key of the system. In this work, a new scheme based on randomizing power consumption of a fixed-operation logic gate is proposed. The goal of this method is enhancing the immunity of AES algorithm against DPA. Having a novel topology to randomize the power consumption of each Exclusive-NOR gate, the proposed circuit causes random changes in the overall power consumption of the steps of the algorithm; thus, the correlation between the instantaneous power consumption and the correct key is decreased and the immunity of the AES implementations which the key is injected into their process through Exclusive-NOR gates is extremely increased. The proposed method can be used as a general hardening method in the majority of cryptographic algorithms. The results of theoretical analysis and simulations in 90-nm technology demonstrate the capability of the proposed circuits to strengthen AES against DPA. The CMOS area and power consumption overhead is less than 1%.